Physiological Response of Broiler Chicken To Cage Temperature - Karnovel, Dody; Hendri, John; Asri, Alfian (Department of Agriculture, 2023)
This study aims to study the physiological response shown by broiler chickens to cage temperatures at different times. A completely randomised design was used in this research, with three treatments and five replications of each. The treatments were the average temperature of the cage in the afternoon (30.15oC) , afternoon (27.04oC), and morning (26.01 °C). Each treatment was repeated six times, and each replication consisted of 5 chickens. The variables measured in this study are respiratory rate, heart rate, and rectal temperature in broiler chickens. If the results of the analysis of variance show that there is a significant difference between treatments, it is continued with the Duncan Multiple Range test. The results showed that the temperature of the cage during the day significantly increased the frequency of breathing of broiler chickens (74.90 times/minute), heart rate (279.50 times/minute), and rectal temperature (41.53 oC) compared to the frequency of breathing (57 times). ,27 times/minute and 55.77 times/minute), heart rate (274.07 times/minute and 272.47 times/minute), and rectal temperature (40.74oC and 40.61oC) In the afternoon and the morning, it can be concluded that the temperature of the cage during the day resulted in the frequency of breathing, heart rate and rectal temperature in broilers which were significantly higher than the temperature of the cell in the afternoon and morning, while the temperature of the cell in In the afternoon, the respiratory frequency, heart rate, and rectal temperature were not significantly higher than the cage temperature in the morning.